Competition and Corruption: How the Level of Competition Affects Corrupt Practices in Public Procurement - Hovhannisyan, David; Hovhannisyan, Tatevik (Bulletin of Yerevan University G: Economics, 2025)
Public procurement plays a crucial role in ensuring effective governance and economic growth, encompassing processes through which governmental entities acquire goods, services, and works. Public procurement has a significant impact on the provision of public services and stimulates economic development. In many countries, public procurement represents a notable portion of government expenditure, often accounting for 15-20% of GDP. The dynamics of public procurement directly affect market behavior, set industry standards, and can promote innovation. Establishing a competitive environment is crucial for enhancing transparency and accountability in procurement processes, which ultimately leads to more efficient use of public funds. Moreover, fostering competition can mitigate anti-competitive practices and reduce the risk of corruption, which is often exacerbated by non-transparent procurement systems. This article employs a qualitative analysis, utilizing insights from public choice theory and examining case studies from Estonia, South Korea, and Armenia to explore the interplay between competition levels in public procurement and the prevalence of anti-competitive behavior and corruption. It emphasizes the importance of institutional frameworks that support competition and transparency to combat corruption and improve public procurement efficacy.